2018
DOI: 10.1371/journal.pone.0204410
|View full text |Cite
|
Sign up to set email alerts
|

Parental costs for in-patient neonatal services for perinatal asphyxia and low birth weight in Ghana

Abstract: The major causes of newborn deaths in sub-Saharan Africa are well-known and countries are gradually implementing evidence-based interventions and strategies to reduce these deaths. Facility-based care provides the best outcome for sick and or small babies; however, little is known about the cost and burden of hospital-based neonatal services on parents in West Africa, the sub-region with the highest global neonatal death burden. To estimate the actual costs borne by parents of newborns hospitalised with birth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Survivors often face lifelong health problems (80%), such as disabilities, developmental delays, palsy, intellectual disabilities, and behavioural problems [7–10]. Furthermore, birth asphyxia places financial and emotional burdens on the families and communities involved [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Survivors often face lifelong health problems (80%), such as disabilities, developmental delays, palsy, intellectual disabilities, and behavioural problems [7–10]. Furthermore, birth asphyxia places financial and emotional burdens on the families and communities involved [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the experiences of LBW and preterm babies have mostly focused on HIV-uninfected mothers' experiences, particularly in the NICU [10,33,35]. They show that mothers of LBW babies experience short and long-term mental health difficulties [13,14,35,57], including depression [58,59], trauma [60] and stress from the economic burden of LBW infant care [46]. We found that HIV stigma, especially experienced immediately after diagnosis, also played a role.…”
Section: Discussionmentioning
confidence: 74%
“…In one study in Ghana, about 75% of mothers with LBW, preterm, and sick infants reported mild to severe symptoms of postpartum depression [13]. Families of LBW/preterm babies in Ghana spend about 8% of their annual income on their care [14]. Caring for a LBW infant in Ghana affects maternal postpartum HIV care practices, including adherence to antiretroviral therapy and retention in clinical care [15].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature showed limited published economic evaluation specific for inpatient neonatal services in Ghana. 14 This study sought to determine the best estimate of actual cost of neonatal services for babies with perinatal asphyxia and LBW/preterm at a district and regional hospital by using a micro-costing approach that examined the process of care. The economic cost of hospital-based neonatal services on families has been described elsewhere.…”
Section: Introductionmentioning
confidence: 99%